A comparison on Wang Yangming’s xin [heart-mind] and Husserl’s ego - Changhua Li (HTS Teologiese Studies/Theological Studies, 2023)
Both Wang Yangming and Husserl adopted a subjective approach to their studies. Wang used his concept of xin [heart-mind] to guide the practice, while Husserl used his concept of ego to discover the truth of objects. A comparison on the descriptions, structures and functions of Wang Yangming’s xin and Husserl’s ego illustrated that xin and ego are different terms for the same thing. The distinction between the two scholars is their differences in teleology and study focus. But their studies can be complementary to extend the knowledge of human beings and benefit scientific research.